Chromosome count, meiotic abnormalities and pollen sterility in Lahaul Sweetvetch (Hedysarum astragaloides Benth. ex Baker, Fabaceae), an endemic and threatened species from India - Kumar, Puneet; Rana, Pawan Kumar; Singhal, Vijay Kumar; Singh, Harminder; Kholia, Bhupendra Singh (Acta Botanica Croatica, 2018)
Male meiotic studies were carried out on eight different accessions of Hedysarum astragaloides Benth. ex Baker (Fabaceae), an endemic and threatened species of northwest Himalaya, India. Although genetic factors such as meiosis, chromosome number, and ploidy level may be causative for the evolution, endemism, rare distribution or even extinction of the species, no detailed information exists. Keeping this in mind H. astragaloides has been studied cytologically. Male meiotic investigations revealed diploid level (2n=2x=14) for species and normal meiotic course in the accessions from the Manali Hills resulting in nearly 100% pollen fertility. However, the accessions scored from the Manimahesh Hills and Pangi Valley depicted inter-pollen mother cell transfer of chromatin material and structural heterozygosity for reciprocal translocations. Consequent upon these meiotic anomalies, some pollen sterility (21%) resulted. On account of this sweeping genetic outcome, the incidence of anomalies such as this in an endemic and threatened species warrants grave consideration. It is sensible to conclude that conservation measures should include the collection of germplasm from the localities where plants are meiotically stable with high gametic fertility, to ensure good germination and healthy plants for future use. Seeds from meiotically normal individuals should be given priority for inclusion in seed banks.